Tumandok on spotlight the perception of non-indigenous viewers of the portrayal of women of indigenous groups as depicted in Amaya - Corpuz, Yvette Mary Louise Pelegrino
This study focused on the portrayal of women of indigenous groups in media, specifically in GMA 7?s epicserye, Amaya. The main objective of this study was to examine the perception of non-indigenous viewers regarding women of indigenous groups in terms of their role and treatment in the family and in the community as depicted in Amaya. The researchers conducted a survey among non-indigenous viewers, as well as interviews with representative of indigenous people?s community and scholars/researchers on Philippine indigenous culture to supplement the results of the survey. Results of the survey showed that majority of the respondents, based on what they have seen in Amaya, perceived women of indigenous groups as slaves and homemakers in the community and family, respectively. Various stereotypes of women depicted in Amaya were also identified in this study and revealed that women were still portrayed in media, generally, as belonging to the private spehere (i.e. the household). This study suggests for future researchers to focus on the perception of indigenous peoples themselves regarding their own depiction in media. Future studies may also focus on the relationship of media with other marginalized sectors of the society.